Branding Institusi Perguruan Tinggi Keagamaan Islam Swasta Di Kawasan Pesisir (Studi Multi Situs Di STITMA Tuban Dan IAI Tabah Kranji Paciran Lamongan) - Sholikah Sholikah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2018)
Abstract, Managers of higher education to innovate and try to develop the institutionsthey lead in order to be better. In general, managing higher education is synonymouswith managing a business organization, which must always adjust the demands ofstakeholders. An urgent matter to be considered in meeting the demands ofstakeholders is to build a good reputation, the results of the study show thatstakeholders prefer to choose reputable organizations. One important aspect inbuilding a good reputation of an organization is to build a positive impression in theeyes of stakeholders, which is a positive impression in the context of marketing can bebuilt through the brand or image of the institution. This study focuses on the issue ofbuilding a brand in the Private Islamic Religious College (PTKIS) located in thecoastal region, namely the Tarbiyah College of Sciences Makhdum Ibrahim Tubanand the Tarbiyatut Tholabah Kranji Islamic Institute of Paciran Lamongan. Theresults of this study are the strategies used by STITMA Tuban and IAI TABAH inbuilding institutional brands in accordance with the strategy of Hermawan KertajayaTriangle GDP, namely: 1) Positioning, which is carried out by making clearinstitutional vision and mission; 2) Differentiation carried out by making distinctivefeatures of each campus, namely STITMA Tuban as a campus that produces educatorswho are professional, religious, and edupraner. Whereas IAI TABAH Kranjo PaciranLamongan as a center for the development of Islamic sciences in the fields ofeducation and non-education; 3) Brand, which is done by making the motto of eachinstitution. Keywords: Branding Institution, PTKIS, STITMA Tuban, IAI TABAH Kranji